Areas of improvement of the budgetary deficit of Ukraine - (:unkn) unknown (Мелітополь: ТДАТУ, 2019)
The state of the budget system can be named as the most important criterion for the economic situation in the country. In the context of financial globalization, the development of the financial system is characterized by a significant increase in the external and internal government debt of the countries of the world
Keywords: budgetary deficit; inflation